Icelandic Greylag Geese wintering in Britain in 1960-1971 - Boyd, H; Ogilvie, M A (Wildfowl, 1972)
Greylag Geese Anser anser breeding in Iceland winter in Scotland, with very small numbers in the north of England and in Ireland. Counts made in Britain in early November each year since 1960 show this population to have increased from about 26,000 in 1960 to over 64,000 in 1970, the rate of growth having slowed since 1966. The geese have been concentrating increasingly in the east and north-east of Scotland, both in November and later in the winter. Mean brood size fell from 3.45 in 1960 to 1.31 in 1968, returning to 2.36 in 1970 but was 1.85 in 1971; the proportion of young birds fell correspondingly, from 43.5% in 1960 to 6.0% in 1968, returning in 1969 and 1970 to very close to the period average of 25.0%. The number of mature geese in the population increased 4-5 times during the decade. In 1960-1962 most of the mature geese in the population seem to have brought families to Scotland; subsequently the proportion of successful mature birds fell to only about 15% in 1968 and up to 40% in 1969-1971. The gross annual mortality rate estimated from the census and age ratio data was only 13.3%. The true rate is probably somewhat greater. There is no good evidence of a trend in annual mortality during this period.